Auditoría financiera y su incidencia en el resultado económico de la ferretería Domínguez, cantón Quevedo, año 2013 - Guncay Boni, Carmen Mercedes (2015)
The development of this thesis includes the application of a "AUDIT FINANCIAL AND ECONOMIC IMPACT ON RESULT OF HARDWARE DOMÍNGUEZ, CANTON QUEVEDO, 2013". Which was made with the intention of analyzing compliance with company policies, the main focus was to assess the level of risk and that these present a degree of reasonableness under the principles and accounting standards to finally issue an audit report according to the results obtained; in conducting this research methods, techniques and research instruments the COSO I, NIAs and IFRS for SMEs which allowed to examine the different aspects involved in the operation of the accounting department of the company, in the company they were used, and now if you are performing controls for the proper development of their daily activities, although there are some shortcomings that can be perfected by executing certain processes for proper decision-making, also the degree of fairness of the financial information was considered reasonably demonstrating financial statements and finally announced the results in a report, for which the relevant recommendations is pointed out, it is suggested to continue complying with International Auditing Standards, the International Financial Reporting Standards for SMEs, as these rules allow meet the objectives. It should be noted that the information is taken faithfully records the company, obtained directly from the owner thereof, used exclusively for academic purposes.